PENERAPAN KONSEP JERA HUKUMAN TAâZIR DALAM PRESFEKTIF MAQASHID SYARIAH (Studi Kasus Penegakan Hukum Pada Masa Syeikh Abdul Wahab Rokan Di Babussalam) - Asmuni, Mustafa Kamal Rokan, Khairunnisak (UIN SU, 2018)
The growing phenomenon of lawlessness in society is one step ahead of the existence of the main source of Islamic law. Any violation of law that is not mentioned in the two main sources of law, the Mujtahids are required to explore new laws in order to realize the purpose of the Sharia. The determination is none other than the kind of tazir finger. The tazir punishment among the scholars has been a difference of opinion but the concept of tazir penalty set by Sheikh Abdul Wahar Rokan in Kampus Babussalam is considered capable marespon social problems that developed in the community when Sheikh Abdul Wahab memipin the village. The results show that the tazir penalty imposed by Sheikh Abdul Wahab Rokan in Kampung Babussalam is an attempt to prevent and educate the perpetrators of the finger and guide him into a better person and person who is aware of the law. This tazir punishment is based on several factors such as Sufism values/teachings of Tarikat Naqsyabandiyah which was taught by Sheikh Abdul Wahab Rokan, and Langkat society condition condition at that time. This tazir punishment can cause deterrent effect for the perpetrator of the finger and also can be enforced with full sense of justice and kemaslahatannya can be felt by all society of Babussalam. Mashlahah is part of the maqashid al-syariyah which aims to protect on five things: keeping the religion (hifzud-din), keeping the soul (hifzhun-nafs), maintaining offspring (hifzhun-nasl), keeping the mind (hifzhul-aql) and keep the property (hifzhul-mal).Â